(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Office procedures set the standard for how staff works together in the office. However, in BCP the researchers observed some various problems in their office procedure and transactions to their customers. The research study focused only in the two departments, the Registrar and M.I.S departments. In registrar the researchers focused on the chronic queue in enrollment of old students with previous balance, re alignment of job description from Department head to Head registrar and loss of documents, and in M.I.S the conflict in updating the balance of the students in their account. The Importance of these studies is to give an enhancement and solutions in problem of the two departments. The researchers used the result of their interviews and survey inside with the two (2) departments. As researchers conducted an interview and survey with the employees inside the two(2) departments on which they are involved to clearly state and identify the main problems of the two(2) department that cause insufficiency in their workflow. Identifying the main problems in processes will help the two (2) departments to find a new way to provide and improve a new working level.The researchers conducted a survey and interview to the two (2) departments the Registrar Office and the Management Information System (M.I S), the stated solution is the result of their answer on the said survey. Based on our survey and interview many respondent agree to the solution such as; in the evaluation of grades having a claiming stab for the student to have a proof that they already paid, in case of misplacing of Official receipt. The process in re alignment of job description of Department Head to Head Registrar for the evaluation of subjects for transferee students. 92 In updating of miscellaneous Balance of Asian United Bank in M.I.S, The M I.S personnel will notify the students using the BCP Portal student account to notify that balance is already updated. 23 On their Clearance, the students can check the additional fees on the KIOS Machine. This enhancement and improvement are agreed by the employees who can help for the growth and stability of the company. The result implies that proposed of the researchers would help the Bestlink College of the Philippines in the near future, enhancing of the two departments will help to be more efficient.